Waiver to apply the European Convention for the Protection of Human Rights and Fundamental Freedoms in the resolution of disputes in the Court of Arbitration for Sport (CAS) - I. A. Vasilyev (Правоприменение)
The subject. Sports legal relations, as having a private legal nature, and assuming “horizontal” inter-subject relations by default, do not imply the extension to them the guarantees provided by international acts in the field of human rights protection in order to protect the individual in “vertical” interaction with public subjects. However, this doctrinal approach is still questioned by sports actors, who make attempts to refute it through the involvement of certain norms of the European Convention for the Protection of Human Rights and Fundamental Freedoms (ECHR) (Articles 6 and 8, mostly) as arguments in sports disputes. An additional incentive for this is the location of international and continental sports federations, their jurisdictional bodies and the Court of Arbitration for Sport (CAS) in the national legal orders that recognize the application of the mentioned ECHR.The purpose of the study. The prospects of arguments in the resolution of sports disputes based on the requirements of the literal use of the norms of the ECHR are considered in this article.Methodology. Methods of analysis and comparison based on the CAS practice.The main results of research and the field of their application. The use of only certain meanings of part 1 of Article 6 of the ECHR in sports justice is forced to be taken into account by CAS due to the prospect of appealing decisions to the Swiss Federal Tribunal.Conclusions. The norms of the ECHR generally do not apply in sports justice.